Association Of Conjunctival Vitreous Reflux With Intraocular Pressure Spikes After Intravitreal Bevacizumab Injection - Kanwal Zareen Abbasi; Ameera Jameel; Muhammad Rizwan Khan; Bilal Humayun Mirza; Salman Tariq; Muhammad Sajid Rafiq Abbasi (Journal of Rawalpindi Medical College)
Objective: To evaluate the effect of conjunctival vitreous reflux on intraocular pressure immediately after intravitreal bevacizumab injection.